Presynaptic Calcium Channel Open Probability and Changes in Calcium Influx Throughout the Action Potential Determined Using AP-Waveforms - Scarnati, Matthew S.; Clarke, Stephen G.; Pang, Zhiping P.; Paradiso, Kenneth G. (Frontiers in Synaptic Neuroscience, 2020)
Action potentials arriving at a nerve terminal activate voltage-gated calcium channels and set the electrical driving force for calcium entry which affects the amount and duration of neurotransmitter release. During propagation, the duration, amplitude, and shape of action potentials often changes. This affects calcium entry, and can cause large changes in neurotransmitter release. Here, we have used a series of amplitude and area matched stimuli to examine how the shape and amplitude of a stimulus affect calcium influx at a presynaptic nerve terminal in the mammalian brain. We identify fundamental differences in calcium entry following calcium channel activation by a standard voltage jump vs. an action potential-like stimulation. We also tested a series of action potential-like stimuli with the same amplitude, duration, and stimulus area, but differing in their rise and decay times. We find that a stimulus that matches the rise and decay times of a physiological action potential produces a calcium channel response that is optimized over a range of peak amplitudes. Next, we determined the relative number of calcium channels that are active at different times during an action potential, which is important in the context of how local calcium domains trigger neurotransmitter release. We find the depolarizing phase of an AP-like stimulus only opens 20% of the maximum number of calcium channels that can be activated. Channels continue to activate during the falling phase of the action potential, with peak calcium channel activation occurring near 0 mV. Although less than 25% of calcium channels are active at the end of the action potential, these calcium channels will generate a larger local calcium concentration that will increase the release probability for nearby vesicles. Determining the change in open probability of presynaptic calcium channels, and taking into account how local calcium concentration also changes throughout the action potential are both necessary to fully understand how the action potential triggers neurotransmitter release.